The effect of development on cortical auditory evoked potentials in normal hearing listeners and cochlear implant users - Jeon, Eun Kyung; Brown, Carolyn; Abbas, Paul; Gantz, Bruce (Frontiers in Human Neuroscience, 2025)
IntroductionCortical auditory evoked potentials (CAEPs), such as the P1-N1-P2 complex (onset response) and the acoustic change complex (ACC), provide insight into sound detection and discrimination. While their developmental trajectories are well documented in normal-hearing (NH) listeners, less is known about how these responses develop in pediatric cochlear implant (CI) users and how they are affected by background noise.MethodsCAEPs were recorded in quiet and +10 dB SNR noise conditions using long-duration vowel stimuli from 91 children and 11 adults with NH and 59 CI users (48 pre-lingually deafened children/young adults and 11 post-lingually deafened adults). Peak latencies (P1, N1, P2) and N1-P2 amplitudes were measured. Developmental effects were analyzed using linear regression, t-tests, and correlation analyses comparing child and adult waveforms.ResultsBoth onset and ACC responses were present across groups, with P1 latency decreasing significantly with age in NH and CI listeners. The ACC followed a similar developmental trajectory as the onset response but matured later, emerging reliably in adolescence. Noise delayed maturation, lengthened latencies, and reduced amplitudes, particularly for the ACC. CI users implanted before 3.5 years showed developmental patterns comparable to NH peers, though both onset and ACC responses were more affected by noise in CI users.Discussion/ConclusionThese findings demonstrate that early implantation supports the typical development of cortical auditory responses, underscoring the importance of neuroplasticity in pediatric CI users. However, the pronounced vulnerability of the ACC to noise highlights ongoing challenges in sound discrimination for CI users. CAEPs, especially ACC measures, may serve as objective markers of auditory maturation and could complement behavioral assessments in clinical practice.